Modified brute force algorithm to solve the closest pair of points problem based on dynamic warping - Rhowel M. Dellosa; Arnel C Fajardo; Ruji P. Medina (Institute of Advanced Engineering and Science, 2019)
This paper introduces an algorithm to solve the closest pair of points problem in a 2D plane based on dynamic warping. The algorithm computes all the distances between the set of points P(x, y) and a reference point R(i, j), records all the result in a grid and finally determines the minimum distance using schematic steps. Results show that the algorithm of finding the closest pair of points has achieved less number of comparisons in determining the closest pair of points compared with the brute force and divide-and-conquer methods of the closest pair of points.